2015
DOI: 10.1016/j.urology.2014.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Outcomes of Prostate Cancer in an Urban Cohort of Predominantly African American, Human Immunodeficiency Virus–infected Patients

Abstract: Objective To determine the clinical presentation and outcomes of prostate cancer in HIV-infected men compared to HIV-uninfected men in an urban setting. Methods A retrospective cohort study of prostate cancer stage at diagnosis and mortality comparing HIV-infected patients to HIV-uninfected patients from 2000 to 2011 was carried out. Clinical features, HIV history, cancer presentation, and outcomes were reviewed. Cox proportional hazards analysis was performed to estimate the association between HIV status a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 22 publications
(29 reference statements)
3
26
1
Order By: Relevance
“…Several studies have reported trends toward a younger age at prostate cancer diagnosis in HIV-infected compared to uninfected men (5, 19, 20). A recent study in the largest HIV cohort in North America found that while age at prostate cancer diagnosis was younger among HIV-infected subjects, the difference was not statistically significant (21); findings were inconclusive with respect to young-onset prostate cancer in groups by HIV status because age was examined in 10-year bins rather than comparing age of young-onset prostate cancer cases by HIV status.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have reported trends toward a younger age at prostate cancer diagnosis in HIV-infected compared to uninfected men (5, 19, 20). A recent study in the largest HIV cohort in North America found that while age at prostate cancer diagnosis was younger among HIV-infected subjects, the difference was not statistically significant (21); findings were inconclusive with respect to young-onset prostate cancer in groups by HIV status because age was examined in 10-year bins rather than comparing age of young-onset prostate cancer cases by HIV status.…”
Section: Introductionmentioning
confidence: 99%
“…American Cancer Society (ACS) guidelines suggest screening at age 40 for men with multiple first-degree relatives with prostate cancer, age 45 for African Americans and men with a single first-degree relative diagnosed with prostate cancer at age < 65, and age 50 for men at average risk. With exception of a study by Riedel et al (5), little is known about young-onset prostate cancer among HIV-infected men in the HAART era. Given the evolving epidemiology of prostate cancer risk in HIV-infected men on newer ART regimens, further study is needed to understand if subpopulations of people living with HIV or AIDS (PLWHA) may be at heightened risk at an earlier age.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations